A critical analysis on International relationships between the IOC and NOC of Sri Lanka. - Wimalasena, Dilan Sandun (Πανεπιστήμιο Πελοποννήσου, 2021)
The Greek Philosopher Aristotle, said in his “POLITICS” book that “man by nature is a social animal. Being a social animal, man can’t live in isolation. His basic nature and his basic needs make him to satisfy his numerous needs in association with others”. In this context, "international relations" are very important. A critical examination has been conducted with regards to the international relations existing between the IOC and NOC of Sri Lanka during the last 3 Olympiads .In order to answer the research question of this study, “How can we analyze the international relations between NOC of sri Lanka (NOC) and the IOC over the last 3 Olympiads, through three main points of good governance, solidarity and education? ”.And qualitative study has been conducted for this study. The objective of this study was to identify the advantageous and favorable conditions of the bilateral relations and to find the ways to strengthen these relations between these two institutions. Data required for the study were gathered through focus groups interviews and documentation. I also used J Nye's concept of soft power to study the behavior of these international relations. Key results of this study generated on three ways. First, how Olympism and the Olympic Movement influenced Sri Lanka from the IOC programmes launched through the Sri Lanka NOC were discussed, secondly, the beneficial and advantageous conditions of these relations were identified, and finally the measures required to uplift these relations were emphasized. The conclusion arrived at the end of this research is that the IOC has been able to achieve their objectives subtly through the international relations maintained with Sri Lanka NOC through various programmes by complying to the concept of Soft Power, and beneficial and favorable conditions have been occurred to both the IOC and Sri Lanka NOC through these relations. The research aims to identify the advantages and disadvantages of international relations between the IOC and the NOC of Sri Lanka, as well as to study how these relations have further developed.
Keywords: International relations; Olympism; Social solidarity; International Olympic Committee; Olympic movement; Διεθνείς σχέσεις; Ολυμπισμός; Κοινωνική αλληλεγγύη; Διεθνής Ολυμπιακή Επιτροπή; Ολυμπιακό κίνημα; Olympism; Olympic Movement; IOC; NOC Sri Lanka; International Relations; Solidarity; Soft Power; Olympic movement